Tingkat Pengetahuan Ibu Hamil Tentang Pengonsumsian Zat Besi Dalam Pencegahan Anemia Selama Kehamilan Di Puskesmas Harapan Raya - Isnaniar; Norlita, Wiwik; Salsabila, Triana (Fakultas MIPA dan Kesehatan, Universitas Muhammadiyah Riau, 2024)
According to the World Healthy Organization (WHO), it is defined that a person is said to be anemic, having haemoglobin (HB) 11 gr/dl during pregnancy and 10 gr/dl postpartum. Anemia can occur due to nutritional deficiencies that have a role in forming haemoglobin such as iron, protein, pridoxin, vitamin B12, vitamin C, folic acid and vitamin E. Vitamin C can play a role in accelerating the absorption of iron in the body. The purpose of this study is to find out the level of knowledge of pregnant women about iron consumption in the prevention of anemia during pregnancy at the Harapan Raya Health Center. The research method used is quantitative descriptive. The data collected used 35 pregnant women respondents who were present at the time of the study using the Accidental Sampling technique. The results of this study can be used as additional information for literature studies and one of the sources of information in health education. From the results of the study data, the researcher found that 21 respondents or equivalent to 60% had good knowledge about iron consumption during pregnancy to prevent anemia during pregnancy. Meanwhile, 14 respondents or as many as 40% have sufficient knowledge related to iron consumption during pregnancy. With good knowledge, of course, it will make a person do a good lifestyle in consuming daily food. So the researcher hopes that pregnant women will continue to maintain knowledge about iron consumption during pregnancy and also to increase knowledge by looking for information that is easy to reach, such as through social media or relatives, neighbors, and friends. So that the health of the mother and baby will remain good with even better maternal knowledge.